Effects of Urinary Kallidinogenase combined with mNGF on neurotrophic status, apoptosis and oxidative stress in patients with ischemic stroke - Qing-Yan Wen (Journal of Hainan Medical University, 2018)
Objective: To study the effects of Urinary Kallidinogenase combined with mouse nerve growth factor (mNGF) on neurotrophic status, apoptosis and oxidative stress in patients with ischemic stroke. Methods: Patients with acute ischemic stroke who were treated in Jiangmen Central Hospital between March 2015 and October 2017 were selected and divided into two groups according to random number table method, the control group received conventional therapy, and the observation group received Urinary Kallidinogenase combined with mNGF therapy on the basis of routine therapy. The contents of neurotrophic cytokines, soluble apoptosis molecules and oxidative stress markers in serum were measured before treatment and 14d after treatment. Results: Serum BDNF, NTF, VEGF, HGF and IGF-1 levels of observation group after treatment were higher than those before treatment whereas serum BDNF, NTF, VEGF, HGF and IGF-1 levels of control group after treatment were not significantly different from those before treatment; serum sFas, sFasL, sTRAIL, 8-OHdG, Hcy and MDA levels of both groups after treatment were lower than those before treatment whereas Livin, Bcl-2, SOD and GSH-Px levels were higher than those before treatment; serum sFas, sFasL, sTRAIL, 8-OHdG, Hcy and MDA levels of observation group after treatment were lower than those of control group whereas BDNF, NTF, VEGF, HGF, IGF-1, Livin, Bcl-2, SOD and GSH-Px levels were higher than those of control group. Conclusion: Urinary Kallidinogenase combined with mNGF can improve the neurotrophic state and inhibit the apoptosis and oxidative stress response in patients with ischemic stroke.